2020
DOI: 10.1109/access.2020.2973177
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Patterns of Visitors in Urban Green Parks by Mining Social Media Big Data Based Upon WHO Reports

Abstract: Green parks in urban areas are believed to enhance the well-being of residents. The importance of green spaces to support health and fitness in urban areas has recently regained interest. Reports released in 2010-2016 by the World Health Organization (WHO) on urban planning, environment, and health stated that green spaces can have a positive impact on physical activity, social and mental well-being, enhance air quality and decrease noise exposure. We analyzed the number of check-ins in various parks of Shangh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 71 publications
0
14
0
3
Order By: Relevance
“…Kernel density estimation (KDE) has been frequently used to quantify the spatial distribution of park visitors across a study area [87,104]. KDE is a statistical approach used to estimate a smooth and continuous distribution from a limited set of observed points [105].…”
Section: Methods Used In Spatial Data Analysismentioning
confidence: 99%
“…Kernel density estimation (KDE) has been frequently used to quantify the spatial distribution of park visitors across a study area [87,104]. KDE is a statistical approach used to estimate a smooth and continuous distribution from a limited set of observed points [105].…”
Section: Methods Used In Spatial Data Analysismentioning
confidence: 99%
“…c) According to the candidate visitors' trajectories and excluding the park staff, we designated candidate visitors who stayed in the park for 0.5-5 h as park visitors. To ensure that the data were representative, we removed parks that attracted fewer than 100 visitors on each study date (Ullah et al, 2020), and visitor volume data were obtained for 86 parks. We further determined each park visitor's gender and age.…”
Section: Data Sourcesmentioning
confidence: 99%
“…In recent years, the use of big data, such as social media and mobile phone data, has gradually gained traction as a new method of studying park visitation patterns in view of the limitations of traditional methods and the rapid development of computer science-and internet-related techniques (Chen et al, 2018;Li et al, 2018;Lin et al, 2021;Song et al, 2020a). Many studies using big data focus on park accessibility (Guo et al, 2019a;Hamstead et al, 2018), the spatial and temporal distribution of urban park users (Chen et al, 2018;Liang and Zhang, 2021;Ullah et al, 2020), and the factors in uencing park usage (Fan et al, 2021;Lyu and Zhang, 2019), with these studies aiming to provide references for the planning and construction of urban parks. Although some previous studies based on questionnaires and interviews have revealed that park visit patterns are in uenced by the visitors' age and gender, unfortunately, such visitor data cannot be easily obtained (Song et al, 2020b;Ullah et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A lot of work has been carried out by using KDE. The previous studies in density estimation from Weibo data mostly used a single technique such as KDE to estimate density on the maps and applied this for a specific task such as gender analysis in green parks and also focused upon the green spaces [22,23], tourism [24,25], and point of interest recommendations [26], etc. Researchers used Weibo to explore the spatial characteristics of check-in data using a single technique; i.e., the spatial analysis of check-in data was carried out using point density in Wuhan [27], and in [28], the authors used KDE to observe gender-based check-in behavior using Weibo data.…”
Section: Related Workmentioning
confidence: 99%